Improvement of energy supply configuration for telecommunication system in remote area s based on improved chaotic world cup optimization algorithm - Li, Huan; Li, Kun; Zafetti, Nicholas; Gu, Jianfeng (Energy (Oxford), 2020)
Generally, using the telecommunication industry in remote rural areas which can’t use the grid is difficult. This issue makes this industry to be extremely dependent on the diesel generators and battery banks for having backup resources. Despite, the unreliability and the environment impacts of these power supplies, using diesel generators is still popular. In this paper, a new clean and optimized configuration based on the proton exchange membrane fuel cell (PEMFC) along with an optimized boost converter unit is proposed for obtaining a reliable source to supply the telecom towers. Using the proposed optimized method makes the cost of telecom companies decreasing. In this study, a feedback controller based on a newly introduced optimization algorithm called improved chaos world cup optimization algorithm is proposed for optimal regulation of the converter unit. The proposed technique provides reliable and high-efficiency performance for the base transceiver station under oscillations on the telecom load and the output voltage of the PEMFC. Simulation results of the proposed optimization method are compared by the traditional Ziegler-Nichols based PI controller and final results showed the superiority of the proposed system. •New optimization algorithm is applied to control the boost converter.•Chaos theory is employed for improving the ability of the optimization algorithm.•New clean configuration based on the PEMFC is introduced.•The PEMFC is utilized as a power supply of BTS of telecom tower.•New optimization algorithm is applied to regulate the PEMFC output.